AB0097 Methotrexate and low dose prednisolone downregulate osteoclast function in monocytes from early rheumatoid arthritis patients. (15th June 2017) - Perpétuo, IP; Caetano-Lopes, J; Rodrigues, AM; Campanilho- Marques, R; Ponte, C; Canhão, H; Ainola, M; Fonseca, JE
Abstract : Background: Rheumatoid arthritis (RA) is a systemic, immune mediated inflammatory disease that is associated with bone erosions and joint destruction. Methotrexate (MTX) slows bone damage but the mechanism by which it acts is still unknown. Objectives: In this study we aimed to assess the effect of MTX and low dose prednisolone (MTX+PDN) on circulating osteoclast (OC) precursors and OC differentiation in RA patients. Methods: RA patients before and at least 6 months after MTX therapy were analyzed and compared with healthy donors. A blood sample was collected in order to assess receptor activator of NF-κB (RANK) ligand (RANKL) surface expression on circulating leukocytes and frequency and phenotype of monocyte subpopulations. Serum quantification of bone turnover markers and cytokines and in vitro OC differentiation assays were performed. Results: The number or RANKL + neutrophils increased in RA patients when compared to healthy donors (p=0.006) and after treatment with MTX+PDN their count was reduced to healthy control numbers (p=0.0155). Classical activation markers of monocytes such as HLA-DR, CD86, CCR2 and CD11b, and also RANK were increased in RA patients at baseline, comparing to control healthy donors. After MTX+PDN exposure, expression decreased to healthy control levels. Serum RANKL levels were increased at baseline comparing to healthy donors (p=0.0164) and normalized after therapy. Although the number of OC was not different between groups, resorbed area and resorbed area/pit were elevated when compared to controls (p=0.0436 and 0.0249, respectively) and reduced after treatment (p<0.0001). Conclusions: Our results suggest that MTX+PDN play an important role in downregulating OC function, which we believe occurs through a decrease in RANK surface expression in monocytes. Disclosure of Interest: None declared